Penerapan Quantum Learning Dengan Congklak Daur Ulang Untuk Meningkatkan Kemampuan Kombinatorik Siswa - Hadi, Satria Purnama; Jubaeni; Tuankotta, Anisa Maulida; Nurrahmah, Arfatin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Recycled congklak is a game that is closely related to mathematics, especially probability. The learning model applied is Quantum Learning in the process of learning mathematics. The purpose of this research is to evaluate the effectiveness of Quantum Learning in improving students' combinatorial ability while providing additional benefits in understanding sustainability through the use of recycled congklak game. The use of experimental research method where students are divided into two classes, namely experimental class and control class. The research sample was students of SMPIT Ar-Rahman Islamic School grade IX. The data analysis process used the SPSS application by conducting various pre-requisite analysis tests and the Mann-Whitney Test and comparing the average N gain value of each class. Recycled congklak learning is very helpful for students in understanding mathematical concepts, especially in probability material and has an effect on students' combinatoric abilities. The application of Quantum Learning implemented in the classroom makes students more active and responsive in listening to learning and guidance.  Keywords: recycled congklak, combinatorics skills, probability, quantum learning.